Crystallization Behavior and Sensing Properties of Bio‐Based Conductive Composite Materials. Issue 2 (13th October 2022) - Abbel, Robert; Greene, Angelique F.; Quilter, Helena; Leveneur, Jérôme; Risani, Regis; Barbier, Maxime; West, Mark; Collet, Christophe; Kirby, Nigel M.; Sorieul, Mathias
Abstract : Poly(3‐hydroxyoctanoate) (PHO), a biocompatible polymer with a skin‐like feel produced by bacterial fermentation, is compounded with carbon nanofibers (CNFs) or carbon black (CB), respectively, to form flexible, 3D printable, bio‐based conductive composites. Conductivities up to 10 and 3 S m −1 can be achieved for CNF and CB, respectively, without negatively affecting the composites' processability. Both filler materials act as nucleating agents for PHO crystallization, significantly accelerating this process which is extremely slow for the filler‐free polymer. Mechanical performance, for example, elastic modulus, is also improved by the addition of CNF or CB. Both types of filler form composites that show a distinct response to mechanical deformation: bending, twisting, and stretching (up to 10% elongation) result in a marked decrease in their electrical resistance (up to 30%). This phenomenon has been exploited to fabricate a 3D‐printed strain sensor that can detect flection and extension via a change in resistance. The results demonstrate the potential of this sustainable biopolymer and its composites for applications in the biomedical space. Abstract : Conductive composites of the biopolymer poly(3‐hydroxyoctanoate and carbon nanomaterials are prepared, and their crystallization kinetics and functional properties are characterized. The materials display a significant reduction in electrical resistance upon mechanical deformation. This behavior is utilized to 3D print a flexible sensor that can reliably detect movement. This work demonstrates the potential of these bio‐based materials for biomedical applications.